Developing human resource capacity to improve awareness and governance in Gari Tourism Village, Gunungkidul - Rusdiyanto, Wahyu; Rachmawati, Indria Desy; Ristini, Deliana (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2025)
This Community Service aimed to train the managers of Gari Tourism Village to improve their knowledge and skills in tourism governance, raise community awareness, and develop local tourism potential. The program was conducted for two days. On June 8, 2024, a presentation on Tourism Awareness, Regional Potential Development, and Community Empowerment for Sustainable Tourism was delivered by Mr. Agung Sulistyo, S.E., M.M., CHE. On June 9, 2024, practical training and mentoring on Tourism Village management were carried out, guided by the same resource person with the service team. The methods used were lectures, discussions, practice, and evaluation. The evaluation results showed that participants’ knowledge and understanding of Tourism Village management significantly improved after the training